1983
DOI: 10.1159/000137881
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional and Pharmacodynamic Characteristics of Brodifacoum in Warfarin-Sensitive Rats

Abstract: A dose-response curve for the hypoprothrombinemic effect of brodifacoum 3-[-3(4’-bromobiphenyl-4-yl) 1,2,3,4-tetrahydronaphth-1-yl]-4-hydroxycoumarin, was constructed using doses ranging from 0.1 to 0.33 mg/kg. Brodifacoum exhibited a remarkably steep dose-response curve. Brodifacoum failed to exhibit a dose-dependent effect on the degradation rate constant (kdeg) for prothrombin complex activity (PCA) after a PCA-synthesis-blocking dose of warfarin. Both phenobarbital pretreatment and SKF525A treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 9 publications
3
62
0
Order By: Relevance
“…The minimal amount of Gla needed for functional activity is not known, not only the number of Gla's but also their position in the molecule is essential (Borowski et al, 1986). For human prothrombin and protein S it was found that the absence of 2 Gla's strongly reduces normal activity (Borowski et al, 1985;Grinnel et al, 1990 Our findings on the kinetics of brodifacoum (0.2mgkg-1) in rat liver are in agreement with those of Bachmann & Sullivan (1983). The compound is extremely slowly eliminated.…”
Section: Discussionsupporting
confidence: 78%
“…The minimal amount of Gla needed for functional activity is not known, not only the number of Gla's but also their position in the molecule is essential (Borowski et al, 1986). For human prothrombin and protein S it was found that the absence of 2 Gla's strongly reduces normal activity (Borowski et al, 1985;Grinnel et al, 1990 Our findings on the kinetics of brodifacoum (0.2mgkg-1) in rat liver are in agreement with those of Bachmann & Sullivan (1983). The compound is extremely slowly eliminated.…”
Section: Discussionsupporting
confidence: 78%
“…However, rats receiving similar sub-lethal doses of brodifacoum showed similar responses; OSP times were elevated more quickly, and returned to normal more quickly (within 4-5 days) than in possums, but brodifacoum residues were again retained in the liver (Bachmann & Sullivan 1983). This implies that possums will have to eat considerably more than 60 g of Talon bait to receive a lethal dose.…”
Section: Discussionmentioning
confidence: 94%
“…Because rodent populations have developed increasing resistance to warfarin through mutations in VKORC1, "superwarfarins" have been developed that are potent VKOR inhibitors with longer half-lives. 26,27 Brodifacoum (the active ingredient of D-Con) is the most commonly encountered rodenticide in the United States, but there are many superwarfarins including coumatetralyl and a growing family of indanediones (eg, bromadiolone, diphenadione). These superwarfarins are not for human use and have the potential to induce a profound and sustained coagulopathy when ingested.…”
Section: Commentsmentioning
confidence: 99%
“…36 Measurements of the plasma half-life of brodifacoum in humans vary, but estimates range from 16 to 36 days. 35,37 Because brodifacoum is fat-soluble, has a very large volume of distribution, is concentrated in hepatocytes, and is 2 orders of magnitude more potent than warfarin, 27,38,39 disruption of the vitamin K cycle can exist far beyond the detection of serum levels, with hemostatic defects extending in some cases beyond a year of ingestion of the superwarfarin. 35 Serial serum brodifacoum levels can be used to approximate elimination kinetics, 36 but these levels do not necessarily correlate with tissue levels.…”
Section: Treatment Of Isolated Deficiency Of Vitamin K-dependent Protmentioning
confidence: 99%